Supermultiplier models, demand stagnation, and monetary policy: Inevitable march to the lower bound for interest rates? - Steven M. Fazzari (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2024)
This article integrates monetary policy into a very simple dynamic supermultiplier model with an accommodating supply side. Results show that monetary policy guided by a conventional Taylor rule may stabilize an economy around the steady-state path of demand-led growth following temporary demand shocks. However, monetary policy is ineffective in offsetting permanent negative demand shocks even if the lower bound for interest rates is not binding. This outcome contrasts with the prevailing view among policymakers that monetary policy can usually assure full utilization of an economy's resources in the long run. The ineffectiveness of monetary policy is particularly acute if autonomous demand grows more slowly than necessary to generate full employment. In this case, if policymakers recognize the under-utilization of resources, monetary policy leads to interest rates trending necessarily to their lower bound. The analysis also shows how monetary policy may lead to counter-productive responses to supply shocks. The article concludes with observations about how the theoretical results correspond with the history of US monetary policy in recent decades.
Keywords: E12; E52; 330; Supermultiplier; Monetary Policy; Demand-Led Growth; Keynesian Macroeconomics